Transfigurasi Filsafat Pendidikan Islam Dari Nalar Konservatif Menuju Rasionalisme Spiritual dan Pragmatisme Transformatif - Umi Salamah; Dirgahayu; Abd. Haris (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study explores the epistemological transformation in Islamic educational philosophy by examining the trajectory from conservative theological frameworks to rational-spiritual and transformative-pragmatic paradigms. Employing a qualitative-descriptive approach through in-depth library research, this article analyzes the conceptual contributions of key figures such as al-Ghazali, Ikhwan al-Shafa, and Ibn Khaldun. The findings indicate that the conservative stream upholds hierarchical classifications of knowledge grounded in scriptural absolutism, whereas the rationalist-religious school advances epistemic potential through the actualization of reason and intellect. Meanwhile, the pragmatic approach advocated by Ibn Khaldun offers a functionalist view of education aligned with sociological needs and empirical realities. Through thematic content analysis, this research affirms the dynamic adaptability of Islamic educational philosophy in addressing the complexities of contemporary civilization. It concludes that an integrative synthesis of ontology, epistemology, and axiology across these philosophical streams can foster a holistic educational model that is both faithful to Islamic tradition and responsive to global intellectual challenges.